Stingless bee honey: Nutraceutical properties and urgent call for proposed global standards - Vit, Patricia; Chuttong, Bajaree; Ramírez-Arriaga, Elia; Enríquez, Eunice; Wang, Zhengwei; Cervancia, Cleofas; Vossler, Favio; Kimoloi, Sammy; Engel, Michael S.; Contreras, Ricardo R.; Mduda, Christopher A.; Tomás-Barberán, Francisco (Trends in food science & technology, 2025)
The traditional uses of stingless bee honey, also known as pot-honey, have accumulated scientific evidence of their nutraceutical utilization as dietary supplement, functional food, and medicinal food to continue innovative developments for expanded applications. The anticataract, anti-inflammatory, antimicrobial, antioxidant, antiproliferative, and neuroprotective bioactivities are nutraceutical properties of stingless bee honey. Proposals of stingless bee honey quality standards have been subject of attention since 2004. The first state norm for Bahia, Brazil (2014) and the six national norms for Malaysia (2017), Tanzania, (2017), Indonesia (2018), Argentina (2019), Australia (2024), and Thailand (2024) evidence perfect timing to escalate the international Codex Alimentarius scenario. This review aims to value the nutraceutical properties of stingless bee honey as a powerful reason of developing proposed global standards by the Codex Alimentarius Commission in the frame of the United Nations-Sustainable Development Goals (UN-SDG): SDG1, SDG2, SDG3. Considering safe health benefits for consumers, the proposal of quality control for biodiverse bee origin of pot-honey, different from Apis mellifera, and the urgent call for global standards. Nutraceutical properties of pot-honey, their active chemical components, and applications were emphasized. The ancestral use for health could impact with innovation while pursuing UN-SDGs. A preliminary dataset of 414 stingless bee honey was prepared to shape global standards. The design of the first Melipona honey norm from the Bahia state, Brazil (2014), and the six national norms from Malaysia (2017), Tanzania (2017), Indonsesia (2018), Argentina (2019), Australia (2024), and Thailand (2024) were contrasted for comparative fit with the CODEX STAN. This accurate evidence-based information is expanding to achieve the historical inclusion by the Codex Alimentarius, to benefit consumers and producers of stingless bee honey, as well as scholars. [Display omitted] •There are 605 species of stingless bees making honey in contrast to the unique Apis mellifera honey.•Nutraceutical biomolecules of bioactive stingless bee honey vary with the associated microbes.•Argentina, Australia, Indonesia, Malaysia, Tanzania & Thailand have national standards for SBH.•Global Stingless Bee Honey Standards are essential for fair honey trade worldwide.•Developing Standards for Stingless Bee Honey is a Codex Alimentarius Commission task.